Clinician Perspectives of Chronic Pain Management in Children and Adolescents with Cerebral Palsy and Dyskinesia. (28th November 2020) - McKinnon, Clare; White, Jennifer; Morgan, Prue; Harvey, Adrienne; Clancy, Catherine; Fahey, Michael; Antolovich, Giuliana
Abstract: Aims: To explore perspectives of clinicians from interdisciplinary teams on the barriers and facilitators to chronic pain management for children and adolescents with cerebral palsy and dyskinesia. Methods: Interdisciplinary focus groups (n = 2) were conducted at two Australian tertiary pediatric hospitals. Twenty-five experienced clinicians took part, including ten physiotherapists, six pediatricians, four rehabilitation physicians, four occupational therapists, and one speech and language therapist. An external moderator conducted the focus groups and data were analyzed using inductive thematic analysis. Results: Four key themes emerged: "balancing the intersection of pain and dyskinesia, " "difficulty communicating between so many providers, " "uncertainty surrounding chronic pain education, " and "differing priorities." Key barriers were identified including a lack of access to some interdisciplinary team members and formalized guidance for health professionals regarding chronic pain education. Conclusion: Key issues were reported to impact the delivery of coordinated inter-disciplinary chronic pain management at the tertiary level for children and adolescents with cerebral palsy and dyskinesia. In the absence of strong evidence, a strategy for implementing effective chronic pain management for children and adolescents with cerebral palsy and dyskinesia and gaining clinician consensus regarding the best practice management are recommended.